Complex Correlation of Two Language Systems: Modern Literary German of Germany and Austrian Variant of German - V. Bondarenko, Elena; V. Dekhnich, Olga; A. Sheifel, Natalia; O. Chernova, Olga; M. Profatilova, Svetlana (Opción, 2019)
This article deals with the linguistic notion “language variation”. Functioning of any language system depends on some characteristic features. Variability consid- ered to be one of the most important of them. Nevertheless “variability” in linguis- tics is still a point for discussion. There are too many scientific definitions of this feature. Different authors understand this term in different ways. The article starts with the analysis of linguistic schools of variability. All of them develop the idea that any language system unit functions in one of its variants, which correlates with the language system level. Variability exists in any time of the system functioning. It changes constantly. The changing happens because of another specific language system characteristic feature – evolution. It occurs under the influence of some inner and outer factors. Premises of the evolution and variability can be found in the language system’s nature, they are formed under certain conditions. The article presents a research of Austrian variant of German lexical variety. German language of Germany is a pluricentric language. It exists in some variants: standard variant of modern literary German of Germany and two variants of German in Austria and Switzerland. The relations between the standard form of the language in Germany and its variant in Austria are the main issue of the research. On the one hand the system of Austrian variant of German is influenced greatly by the system of Ger- man language in Germany, but on the other hand this variant of German exists in a separate territory of Austria, where it depends on economic, social, historical and cultural factors of the country. The article shows that there are differences in all the language system levels, but especially on its lexical level. The article provides some examples of Austrian variant of German to illustrate the authors’ point of view and gives some information to prove the hypothesis: the Austrian variant of German has strong ties with the system of German language of Germany, but it develops in its own way due to some internal and external factors.